Model Pendidikan Interprofesional Dalam Upaya Peningkatan Kemampuan Kolaboratif Mahasiswa Kesehatan - Lia Mulyati; Mamlukah .; Mala Trimarliana (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
The public demand for the quality of health services continues to increase, patients get interventions from various health professions to address their health problems with their respective analysis and intervention, so frequent repeated reviews and multiple interventions will require professional collaboration. The purpose of this study is to analyze the effectiveness of the model of interprofesional education to increase the collaborative skills of health students. Types of research mix methods between quantitative and qualitative. Data collection with triangulation through instrument used questionnaire, FGD guidance and semi structured interview. A sample of 20 people consisting of 8 students of nursing, 5 students of public health and 7 midwifery students by following the process of learning together for eight weeks. Result of improvement of student perception toward interprofesional education with average difference 1.7 (P: 0.02), Collaborative ability happened significant improvement between before and after interprofesional education with difference average 3,4 (P 0.025). Student attitudes towards team work with an average difference of 7.3 (P: 0.003). Interprofesional education with problem based learning methods is very effective for improving collaborative skills, and providing cooperative experience. The success of interprofesional education is strongly supported by clarity of objectives and learning topics as well as the breadth of insights and experiences of tutor or facilitator clinics.